2022
DOI: 10.1111/aswp.12250
|View full text |Cite
|
Sign up to set email alerts
|

“We'll starve to death”: The consequences of COVID‐19 over the lives of poor people with disabilities in rural Nepal

Abstract: There is no doubt that the sudden outbreak of COVID‐19 negatively impacted billions of people worldwide, and among them, people with disabilities became most susceptible. However, little is known about the impact of COVID‐19 on the lives of people with disabilities in Nepal. Using empirical data from semi‐structured in‐depth interviews with people with disabilities, disability specialist, and community leaders, this study discusses the lived experiences of people with disabilities who have been affected by COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Research shows that intersectional stigma consistently negatively affects health outcomes (40). Our research and other research from Nepal show that for some caregivers and people with disabilities the COVID-19 mitigation measures were more stressful than for other families (35,48,49). Considering their prior experience of social exclusion and its' effects, they faced heightened distress from social distancing measures, particularly when they were ill. Access to healthcare is limited for people in rural Nepal and this difficulty is exacerbated for those with disabilities who often need additional support to reach care (50,51).…”
Section: Intersectional Stigmamentioning
confidence: 50%
“…Research shows that intersectional stigma consistently negatively affects health outcomes (40). Our research and other research from Nepal show that for some caregivers and people with disabilities the COVID-19 mitigation measures were more stressful than for other families (35,48,49). Considering their prior experience of social exclusion and its' effects, they faced heightened distress from social distancing measures, particularly when they were ill. Access to healthcare is limited for people in rural Nepal and this difficulty is exacerbated for those with disabilities who often need additional support to reach care (50,51).…”
Section: Intersectional Stigmamentioning
confidence: 50%
“…Whilst the broader evidence base about the levels of income and multidimensional poverty of persons with disabilities and their families has grown in the last ten years, no study analy-ses whether poverty has changed over time for households and persons with disabilities in Latin America. Similarly, whilst the number of studies analysing the potential effect of the Covid-19 pandemic on the levels of poverty of individuals and households with members with disabilities has increased ( Bargain & Aminjonov, 2021 ; Goyal et al, 2023 ), few studies have analysed how the pandemic affected the levels of income and multidimensional poverty of persons with dis-abilities ( Sarker et al, 2022 ; Senjam, 2020 ). The main findings of studies that include a specific focus on disability are that persons with disabilities have faced an increasing or higher number of barriers to accessing healthcare ( Sarker et al, 2022 ; World Health Organization (WHO), 2022 ; Lebrasseur et al, 2021 ); that they were left out of most Covid-19 related education strategies ( Croft & Fraser, 2021 ); and that the levels of poverty (income and multidimensional) have increased in a larger proportion than for those without disabilities ( Sarker et al, 2022 ; United Nations (UN), 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ]. Studies have shown that the pandemic has affected the mental health of PWDs [ [22] , [23] , [24] ], their economic status [ 25 ], and their access to resources and services [ 16 , 18 , 24 , 26 ]. In addition, PWDs have often been especially vulnerable to the virus itself as a result of a lack of knowledge, pre-existing health conditions, barriers to accessing health and hygiene measures, and their reliance on personal carers making it impossible to maintain social distance [ 2 , 7 , 27 ].…”
Section: Introductionmentioning
confidence: 99%